Muscle fiber type characterization and myosin heavy chain (MyHC) isoform expression in Mediterranean buffaloes - Francisco, C. L. [UNESP]; Jorge, Andre Mendes [UNESP]; Dal-Pai-Silva, M. [UNESP]; Carani, F. R. [UNESP]; Cabeço, Ludimila Canuto [UNESP]; Silva, S. R. (Elsevier B.V., 2011)
This study aimed to evaluate myosin heavy chain (MyHC) isoform expression and muscle fiber types of Longissimus dorsi (LD) and Semitendinosus (ST) in Mediterranean buffaloes and possible fibers muscles modulation according to different slaughter weights. The presence of MyHC lib isoforms was not found. Only three isoforms of MyHC (Ila, Ilx/d and I) were observed and their percentages did not vary significantly among slaughter weights. The confirmation of the presence of hybrid muscles fibers (IIA/X) in LD and ST muscles necessitated classifying the fiber types into fast and slow according to their contractile activity, by m-ATPase assay. For both muscles, the muscle fiber frequency was higher for fast than for slow fibers in all weight groups. There was a difference (P<0.05) in the frequency of LD and ST muscle fiber types according to slaughter weights, which demonstrate that the slaughter weight influences the profile of muscle fibers from buffaloes. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: River buffalo; Skeletal muscle; Electrophoresis